How can biophotonics help dentistry to avoid or minimize cross infection by SARS-CoV-2? - Besegato, João Felipe [UNESP]; de Melo, Priscila Borges Gobbo [UNESP]; Tamae, Patrícia Eriko [UNESP]; Alves, Ana Paula Aparecida Raimundo [UNESP]; Rondón, Luis Felipe [UNESP]; Leanse, Leon G.; dos Anjos, Carolina; Casarin, Heitor Hussni; Chinelatti, Michelle Alexandra; Faria, Gisele [UNESP]; Dai, Tianhong; Bagnato, Vanderlei Salvador; et al. (Elsevier, 2022)
Biophotonics is defined as the combination of biology and photonics (the physical science of the light). It is a general term for all techniques that deal with the interaction between biological tissues/cells and photons (light). Biophotonics offers a great variety of techniques that can facilitate the early detection of diseases and promote innovative theragnostic approaches. As the COVID-19 infection can be transmitted due to the face-to-face communication, droplets and aerosol inhalation and the exposure to saliva, blood, and other body fluids, as well as the handling of sharp instruments, dental practices are at increased risk of infection. In this paper, a literature review was performed to explore the application of Biophotonics approaches in Dentistry focusing on the COVID-19 pandemic and how they can contribute to avoid or minimize the risks of infection in a dental setting. For this, search-related papers were retrieved from PubMED, Scielo, Google Schoolar, and American Dental Association and Centers for Disease Control and Prevention databases. The body of evidence currently available showed that Biophotonics approaches can reduce microorganism load, decontaminate surfaces, air, tissues, and minimize the generation of aerosol and virus spreading by minimally invasive, time-saving, and alternative techniques in general. However, each clinical situation must be individually evaluated regarding the benefits and drawbacks of these approaches, but always pursuing less-invasive and less aerosol-generating procedures, especially during the COVID-19 pandemic.
Keywords: Aerosol; Antimicrobial blue light; Antimicrobial photodynamic therapy; Biofilm; Biophotonics; COVID-19; COVID-19 dentistry biosafety; Cross-infection; Dental caries; Dentistry; Endodontic treatment; Endodontics; Laser therapy; Oral decontamination; Oral soft tissues; Periodontal disease; Periodontics; Photobiomodulation; SARS-CoV-2; UVC decontamination